Does Aggregate Profitability Really Matter? - Glyn, A (1997)
The impact of profitability on capital accumulation, neglected in conventional accounts, is confirmed by a cross-sectional analysis of the postwar experience of manufacturing in OECD economies which is consistent with a body of time-series and firm-level studies. The effect of capital accumulation on growth is reviewed, suggesting a somewhat stronger impact than growth accounting assumed. Profitability recovered in most, but not all, OECD economies in the 1980s and the recovery was strongest where unemployment rose most and where labor cost competitiveness improved. The response of manufacturing investment was very patchy, however, and a number of influences that may have weakened the link to achieved profitability are discussed.